2007
DOI: 10.1021/ja073944y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Grafting of n-Alkenes onto Carbon Surfaces:  the Role of Photoelectron Ejection

Abstract: The grafting of molecular layers to carbon-based materials provides a way to combine the high chemical and thermal stability of these materials with surface properties such as chemical recognition or reactivity. The functionalization of surfaces with ultraviolet light has emerged as a way to modify difficult-to-functionalize materials, such as diamond. We have performed a combined experimental and computational investigation of the photochemical reaction of terminal alkenes with hydrogen-terminated carbon surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
172
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(200 citation statements)
references
References 91 publications
27
172
1
Order By: Relevance
“…Nucleophilic attack by the electron-rich alkene group then grafts the molecules to the diamond surface. Experimental and computational results show that reactivity of different alkenes correlates with the electron affinity of the "R" group (24,28,38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleophilic attack by the electron-rich alkene group then grafts the molecules to the diamond surface. Experimental and computational results show that reactivity of different alkenes correlates with the electron affinity of the "R" group (24,28,38).…”
Section: Resultsmentioning
confidence: 99%
“…While the surface chemistry of carbon is relatively unexplored, in recent work we have shown that photochemical grafting of organic alkenes can provide an extremely robust way to link functional organic molecules to surfaces of carbon, including diamond (22)(23)(24)(25)(26), amorphous carbon (23,27,28), glassy carbon (29), and carbon nanofibers (30,31). Carbon surfaces functionalized in this manner have shown excellent stability, even at elevated temperatures (32).…”
mentioning
confidence: 99%
“…TFAAD is used because it has excellent grafting properties, because it can be easily detected via x-ray photoelectron spectroscopy (XPS), and because it is a precursor to amine-modified surfaces that are useful for subsequent modification with DNA or proteins. [1] In recent work on carbon surfaces we found that TFAAD is also an exceptionally good molecule to use because its chemical structure facilitates initiation of the grafting reaction [23,24]; a more detailed discussion of the mechanism on metal oxides and use of other molecules will be reported separately. Here, we report on (bio)molecular layers formed using TFAAD.…”
Section: Grafting Of Molecular Layersmentioning
confidence: 99%
“…It is the hydrogen on the surface that enables the later photochemical grafting of functional molecules, [10] thus the ERDA results suggest that the hydrogen plasma treatment is the superior modification method in this respect. However, the STM and SIMS PCA results showed that the hydrogen plasma treatment causes greater disruption and etching of the surface, which in turn is likely to have detrimental implications (on factors such as electron transduction and transport from sensing molecules to the substrate) for the success of electrochemical sensor applications.…”
Section: Stmmentioning
confidence: 99%